2007
DOI: 10.1159/000107429
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Behavioral Inhibition and Maternal Symptoms of Depression

Abstract: Background: The significance of behavioral inhibition in the second year of life for the development of social phobia in later childhood was the incentive to explore whether maternal postnatal psychopathology is a predictor for behavioral inhibition in the offspring. Method: 101 mother-infant pairs were recruited from local obstetric units and examined for maternal psychopathology by the Symptom Checklist and the Edinburgh Postnatal Depression Scale several times during the first postnatal year. Child behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 52 publications
(31 reference statements)
3
28
1
4
Order By: Relevance
“…It is related to impaired functioning and also impacts the child of the affected mother, with psychological and behavioral problems occurring beyond infancy and into childhood (Hay et al, 2001;Moehler et al, 2007;Murray, Fiori-Cowley, Hooper, & Cooper, 1996;Ramchandani, Stein, Evans, & O'Connor, 2005;Weinberg & Tronick, 1998).…”
Section: Postpartum Depressionmentioning
confidence: 99%
“…It is related to impaired functioning and also impacts the child of the affected mother, with psychological and behavioral problems occurring beyond infancy and into childhood (Hay et al, 2001;Moehler et al, 2007;Murray, Fiori-Cowley, Hooper, & Cooper, 1996;Ramchandani, Stein, Evans, & O'Connor, 2005;Weinberg & Tronick, 1998).…”
Section: Postpartum Depressionmentioning
confidence: 99%
“…With regard to depression, two family studies observed elevated rates of BI among offspring of depressed parents [Kochanska, 1991;Rosenbaum et al, 2000], although a third study did not [Kochanska and Radke-Yarrow, 1992]. Another recent study found that child BI at 14 months was associated with depression in mothers at 4 months post-partum [Moehler et al, 2007]. A long-term prospective study of an epidemiologic sample also found links between inhibited behavior at age 3 (observed by examiners during a cognitive assessment) and major depression in early adulthood [Caspi et al, 1996]; in particular, with depression which onset in childhood and recurred in adulthood [Jaffee et al, 2007].…”
Section: Questions About Other Risks Conferred By Bimentioning
confidence: 99%
“…Women who suffer from PPD experience feelings of inadequacy and hopelessness, which can often persist from months to years after childbirth. The damaging role that PPD plays in the mother-infant relationship may result in suboptimal cognitive and emotional development in the child, which can subsequently increase the risk of depression in the child into adolescence (Ramchandani et al, 2005;Murray and Cooper, 2003;Goodman et al, 1993;Downey and Coyne, 1990;Rahman et al, 2004;Sinclair and Murray, 1998;Moehler et al, 2007;Murray et al, 2011). Although psychosocial aspects of PPD are well researched, there is a dearth of biological investigations into the pathophysiology of this disorder.…”
Section: Introductionmentioning
confidence: 99%